2016
DOI: 10.1016/j.psyneuen.2016.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment effects of early life stress in adolescents can be predicted with early biomarkers: Impacts of sex, experience, and cytokines

Abstract: Childhood adversity increases vulnerability to psychiatric disorders that emerge in adolescence, in a sex-dependent manner. Early adversity modeled in rodents with maternal separation (MS) affects cognition and medial prefrontal cortex (mPFC) circuitry. Humans and animals exposed to early life adversity also display heightened circulating inflammatory cytokines, however the predictive relationship of these early measures with later behavioral deficits is unknown. Here, male and female rats were exposed to MS o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
98
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(124 citation statements)
references
References 64 publications
(80 reference statements)
10
98
2
2
Order By: Relevance
“…In line with that, we also found more evidences pointing to a decrease mRNA GR and MR expression within brain tissues of maternal separated animals. Another emergent hypothesis corroborated by our findings is related to the imbalance of the immune system because of stressful conditions, corroborating reported findings from rats (Grassi-Oliveira et al, 2016) and human ELS studies (Black, 2002;Coelho et al, 2014).…”
Section: Maternal Separation Effects On Biological and Behavioural Phsupporting
confidence: 92%
“…In line with that, we also found more evidences pointing to a decrease mRNA GR and MR expression within brain tissues of maternal separated animals. Another emergent hypothesis corroborated by our findings is related to the imbalance of the immune system because of stressful conditions, corroborating reported findings from rats (Grassi-Oliveira et al, 2016) and human ELS studies (Black, 2002;Coelho et al, 2014).…”
Section: Maternal Separation Effects On Biological and Behavioural Phsupporting
confidence: 92%
“…Stressors occurring during sensitive periods may have profound effects on development of brain, cognition, and behavior by altering the organization of neural circuits, which in turn may lead to increased risk for psychopathology and negative health outcomes (Gilbert et al, 2009; Heim and Nemeroff, 2001; Sánchez et al, 2001). Further, early life stress can induce early vaginal opening in female rats (Grassi-Oliveira et al, 2016) and may interact with puberty to exacerbate the rise in psychopathology during early puberty (Fig. 5; Silberg et al, 1999).…”
Section: How Does the Function Of Associative Neocortex Change Durmentioning
confidence: 99%
“…These structural changes are accompanied by changes to cognition supported by frontal circuits (Lovic and Fleming, 2004; Thomas et al, 2015; Yang et al, 2015). Interestingly, early life adversity may accelerate brain development (Callaghan et al, 2014; Hostinar and Gunnar, 2013), puberty onset (Belsky et al, 1991; Ellis et al, 1999; Grassi-Oliveira et al, 2016), maturation of fear extinction/recovery behavior (Callaghan and Richardson, 2011), attachment and avoidance learning (Moriceau et al, 2009), reversal learning (Thomas et al, 2015), and maturation of frontal-amygdala connectivity (Gee et al, 2013). This accelerated brain development following early life stress may be an adaptive mechanism that coordinates the development of neural circuits to meet the demands of an adverse environment (Callaghan et al, 2014; Hostinar and Gunnar, 2013).…”
Section: How Does the Function Of Associative Neocortex Change Durmentioning
confidence: 99%
“…For example, we recently observed that postnatal stress in rats caused by maternal separation from postnatal day (P) 2-20 yields a decrease in circulating levels of the anti-inflammatory cytokine IL-10 at P35, but not P25 nor P55 (Figure 2). This transient decrease occurred in adolescent males, but not females (Grassi-Oliveira et al, in press). In support of the idea that adolescent changes in circulating cytokines can predict altered behavioral outcomes, we found that lower levels of circulating peripheral IL-10 at P35 predicted poor performance in the win-shift cognitive behavioral task two weeks later, only in maternally separated male rats (Grassi-Oliveira et al, in press).…”
Section: Missing “Links”: the Blood-brain Interfacementioning
confidence: 81%
“…This transient decrease occurred in adolescent males, but not females (Grassi-Oliveira et al, in press). In support of the idea that adolescent changes in circulating cytokines can predict altered behavioral outcomes, we found that lower levels of circulating peripheral IL-10 at P35 predicted poor performance in the win-shift cognitive behavioral task two weeks later, only in maternally separated male rats (Grassi-Oliveira et al, in press). Adolescence may therefore be a period during which early-life stressors or events that “derail” development can manifest in immune dysfunction, with consequences for the brain and long-term behavioral outcomes.…”
Section: Missing “Links”: the Blood-brain Interfacementioning
confidence: 81%